Hubungan Perilaku Menjaga Kebersihan Genetalia Eksterna Dengan Penyakit Keputihan - Ayu Dita; Fitri SH (Citra Delima : Jurnal Ilmiah STIKES Citra Delima Bangka Belitung, 2021)
Based on research data on women's reproductive health, it shows that 75% of women in the world must suffer from vaginal discharge, at least once in their life. Treatment of external genitalia that is not good will be a trigger for vaginal discharge. The fact is that many young women do not understand and care about how to care for their reproductive organs. The purpose of this study was to determine the relationship between the behavior of maintaining external genetalia cleanliness and vaginal discharge in high school students of SMAN 3 Pangkalpinang in 2016. This research method was a descriptive analytic survey with a cross sectional design, this study was conducted on 26-31 May 2016, the population of this study was 156 female students and a total sample of 125 students of class X and XI SMAN 3 Pangkalpinang 2016. Data was collected by filling out a guided questionnaire that had been tested, sampling using quota sampling and univariate and bivariate data analysis using the chi square test with degrees of confidence 95%. The test results showed that there was a significant relationship between the behavior of maintaining external genetalia cleanliness and vaginal discharge, namely knowledge (p = 0.000, POR = 6.375), attitude (p = 0.000, POR = 5.189), action (p = 0.001, POR = 5.280), The most dominant relationship with leucorrhoea is knowledge (POR: 6,375).